THE EFFECTIVENESS OF EDUCATIONAL VIDEO MEDIA AND INTERACTIVE APPLICATIONS IN INCREASING STUDENT MOTIVATION IN THE DIGITAL ERA - Fitri Handayani; Muhammad Hasan Basari; Ari Pratama Putra; Rachmat Efendi; Syukron Jamal; Muhammad Ridwan (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study is motivated by the low learning motivation of vocational high school (SMK) students who still rely on conventional teaching methods amid the rapid development of the digital era. This study aims to describe the effectiveness of educational videos and interactive applications in improving students’ learning motivation. The research employed a descriptive method with a qualitative approach, using data collection techniques including interviews, observations, and document analysis. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that the implementation of educational video media and interactive applications is effective in enhancing students’ learning motivation, improving their understanding of the learning materials, and increasing their engagement, enthusiasm, and learning independence. In addition, digital media provide more engaging, enjoyable, interactive, and contextual learning experiences. The findings conclude that the integration of educational videos and interactive applications is an effective strategy for improving vocational students’ learning motivation in the digital era. This study is expected to contribute theoretically as a reference for future research and practically for educators in developing innovative digital-based learning